2021
DOI: 10.21203/rs.3.rs-711763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tuning the Structural Isomers of Phenylenediammonium Cations to Afford Efficient and Stable Perovskite Solar Cells and Modules

Abstract: Organic halide salt passivation is considered to be an essential strategy to reduce defects in state-of-the-art perovskite solar cells (PSCs). This strategy, however, suffers from the inevitable formation of in-plane favored two-dimensional (2D) perovskite layers with impaired charge transport, especially under thermal conditions, impeding photovoltaic performance and device scale-up. To overcome this limitation, we studied the energy barrier of 2D perovskite formation from ortho-, meta- and para-isomers of (p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, the two peaks located at 286.0 eV in C1s and 400.3 eV in N1s (Figure 2c) are attributed to the GA group, combined with the TGA (Figure S4b,c, Supporting Information), indicating that GA cation and GCA additive exist in CsPbTh 3 film. [31,40,41] Notably, as shown in Figure 2d and Figure S5 (Supporting Information), the peak positions of Pb4f, Cs3d, and I3d shift to higher binding energy after coincorporation of GA cation, Ac anion, and GCA, likely due to increased formation energy. [39,42] These results are mainly attributed to the GA with six H bonds partially substituting Cs, which can reduce the H-I distance and suppress iodide ion diffusion.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the two peaks located at 286.0 eV in C1s and 400.3 eV in N1s (Figure 2c) are attributed to the GA group, combined with the TGA (Figure S4b,c, Supporting Information), indicating that GA cation and GCA additive exist in CsPbTh 3 film. [31,40,41] Notably, as shown in Figure 2d and Figure S5 (Supporting Information), the peak positions of Pb4f, Cs3d, and I3d shift to higher binding energy after coincorporation of GA cation, Ac anion, and GCA, likely due to increased formation energy. [39,42] These results are mainly attributed to the GA with six H bonds partially substituting Cs, which can reduce the H-I distance and suppress iodide ion diffusion.…”
Section: Resultsmentioning
confidence: 94%
“…As a result, unencapsulated DJ 2D–3D PSCs provided a maximum performance of 21.6% and excellent strength at 85% relative humidity, far outperforming their RP 2D–3D and 3D equivalents. More recently, Lui et al [ 105 ] studied the energy barrier of 2D DJ perovskite formation with different isomer of phenylenedi(ethylammonium) iodide (PDEAI) to passivate imperfections in perovskite solar cells. An examination of the ortho ‐, meta ‐, and para ‐isomers of PDEAI 2 revealed that the ortho ‐isomer efficiently improves the energy barrier of 2D perovskite generation and hinders bulky organic cations from reaching the perovskite lattice even at high temperatures.…”
Section: Diammonium Cations For 2d Halide Organic–inorganic Perovskit...mentioning
confidence: 99%
“…As a result, unencapsulated DJ 2D-3D PSCs provided a maximum performance of 21.6% and excellent strength at 85% relative humidity, far outperforming their RP 2D-3D and 3D equivalents. More recently, Lui et al [105] studied the energy barrier of 2D DJ Figure 9. a) Schematic illustration of the preparation of pristine and DMEDAI 2 -treated perovskite thin films and b) steady-state PL spectra of perovskite thin films with and without the DMEDAI 2 treatment (architecture: glass/perovskite).…”
Section: D/3d Hierarchical Heterojunction Structurementioning
confidence: 99%
“…Organic-inorganic hybrid perovskite solar cells (PSCs) have gained considerable interest in the last decade on account of their excellent photoelectric properties and low processing cost. [1][2][3] The power conversion efficiency (PCE) of these devices has reached a record value of over 25%, comparable to that of silicon solar cells with the best performance. 4 However, the current PCE of PSCs is still lower than the theoretical limit of Shockley-Queisser.…”
Section: Introductionmentioning
confidence: 96%